Finders keepers : a novel - King, Stephen, 1947- (New York : Scribner, 2015)
Wake up, genius. So begins Kings story about a vengeful reader. The genius is John Rothstein, an iconic author who created a famous character, Jimmy Gold, but who hasnt published a book for decades. Morris Bellamy is livid, not just because Rothstein has stopped providing books, but because the nonconformist Jimmy Gold has sold out for a career in advertising.
Maine author.bStephen King lives in Bangor, Maine.
Keywords: Authors -- Crimes against -- Fiction; Fans (Persons) -- Fiction; Psychopaths -- Fiction; Recluses -- Fiction; Suspense fiction